Isolation, purification, and characterization of polysaccharides from Dendrobium findlayanum: biological activities and potential therapeutic applications - Chen, Ji; Li, Linhong; Mo, Xu; Wu, Lijuan; Zhang, Chaowen; Sun, Yu; Liu, Yao; Li, Rui; Zou, Yuanfeng; Zheng, Yan; Liu, Fan; Tian, Mengliang (Frontiers in Nutrition, 2025)
The crude polysaccharides of Dendrobium findlayanum were extracted by ethanol precipitation and separated using DEAE Sepharose Fast Flow and Sepharose 6 Fast Flow chromatography to obtain DFP-NP and its purified fraction DFP-NP1. Structural characterization revealed that DFP-NP (12.3 kDa) primarily consisted of mannose, rhamnose, glucose, and galactose in a molar ratio of 11.61:0.68:84.78:2.93, with FT-IR spectra confirming typical polysaccharide functional groups. In vitro assays demonstrated that DFP-NP1 polysaccharides at concentrations of 5.0–20 μg/mL enhanced CAT and SOD activities and upregulated related gene expression in IPEC-J2 cells, while reducing TNF-α, IL-1β, and IL-6 secretion. They decreased expression levels of genes associated with the antioxidant signaling and cellular inflammatory pathways in IPEC-J2 cells. Therefore, D. findlayanum polysaccharides possess significant potential for application as a nutraceutical supplement to alleviate intestinal inflammation linked to oxidative stress, leveraging a dietary approach for health maintenance.